Morphometric features of topmouth gudgeon Pseudorasbora parva (Temminck & Schlegel, 1846) in the HirfanlÄ± Reservoir, Turkey - Benzer, Semra (Acta Aquatica: Aquatic Sciences Journal, 2020)
The aim of this study was to some morphometric characteristics of Pseudorasbora parva from HirfanlÄ± Reservoir, Turkey. A morphological analysis of 29 morphometric characters were performed. These characteristics head length; preorbital distance; eye diameter; postorbital distance; head depth; predorsal distance; prepelvic distance; preanal distance; pectoral fin-pelvic fin (P-V) distance; pelvic fin- anal fin (V-A) distance; body depth (18 perpendicular); dorsal fin (anterior end)-anal fin distance (Da-A); dorsal fin (posterior end)-anal fin distance (Dp-A); postdorsal distance; postanal distance; caudal (C) peduncle length (dorsal); caudal peduncle length (ventral); caudal peduncle depth; dorsal fin (D) base length; anal fin (A) base fin length; pectoral fin (P) length; pelvic (V) fin length; caudal upper lobe length; caudal fork length; caudal lower lobe length; dorsal fin length; anal fin length; gape. The samples were measured weight to the nearest 0.01g and total, fork and standard length to the nearest 0.01 mm. The total length (TL) ranged from 4.10 cm to 9.30 cm and body weight ranged from 0.600 to 7.137 g.Keywords: Pseudorasbora parva; topmouth gudgeon; morphometric properties; HirfanlÄ± Reservoir